RANCANG BANGUN SISTEM INFORMASI PENGAWASAN PEMASANGAN JARINGAN LISTRIK PADA PT.PLN (Persero) AREA PALEMBANG - Vivi Sahfitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
Installation of electrical network at PT. PLN (Persero) is done by a vendor that works with the agency. Before the installation of the electricity network the vendors must fill the data first to know the responsibility of each job in the installation of electrical networks. The problem in this research is that there is no specific system used in the collection of vendors. This research aims to design and build an application that can help PT. PLN (Persero) in supervising the electrical network installation conducted by the Vendor. The research method used is the Development research method, which is a research activity aimed at and develop or complete knowledge that is already know. The development system used is web Engineering. The results of the research is the information system of installation control electrical network that can help PT. PLN (Persero) in data and supervise the work that is done by the vendor so that the performance produced better and increase customer satisfaction. Keywords: Sistem Informasi, Pengawasan, Web Engineering, Berbasis Web